Research of microorganisms, parasites and dirt in drumsticks sold by street vendors (Research, Society and Development, 2020)
It is of great importance to maintain the hygienic-sanitary quality of food and places where it is handled and marketed. This work aimed to evaluate the hygienic-sanitary conditions of Brazilian croquettes with chicken filling sold by street vendors in the city of Mossoró, state of Rio Grande do Norte. Ten samples were subjected to counting aerobic mesophilic bacteria, counting fungi and yeasts, Salmonella spp., Coliforms at 35ºC and 45ºC. The research was into find dirtiness and pathogenic parasites was carried out with the flotation and sedimentation test. Total coliforms were found in 30% (3/10) of the samples evaluated, with values ​​ranging from 1100 NMP / g and the presence of thermotolerant coliforms in 10% (1/10) with a value greater than > 1100 NMP / g. The count of mesophilic bacteria varied from 3.17 to 6.23 (Log10 UFC/g). While the mold and yeast count between 3.69 to 5.55 (Log10 UFC/g). Regarding the analyzes of Salmonella ssp., Escherichia coli and pathogenic parasites were negative. The results allowed to conclude that, of the total of ten samples analyzed, 10% (1/10) was unfit for human consumption.